Undergraduate College Student Dependence on Smartphone and Its Effect to Purchase Intention in Indonesia - Roy Poan; Mathias Ben Hardi; Muana Nanga (President University, 2022)
Purpose - This research was aimed to examine the factors that influence student dependence on smartphones and its effect to purchase intentionDesign/methodology/approach – Quantitative research method used in this research with the Partial Least Square (PLS) path modeling approach and structural equation modeling (PLS-SEM) technique to test the proposed hypothesis. From 442 total questionnaire responses, 368 valid responses were collected and being tested using SmartPLS.Findings – This research found that Social Needs, Social Influence, and Convenience significantly affecting student Dependence on Smartphone. A similar result also found that Social Needs, Social Influence, and Convenience significantly affect purchase intention. For the dependent variable, Dependence on Smartphone significantly affects Purchase Intention. However, Social Needs were found to have the most significant influence on Dependence on Smartphone and Purchase Intention.Originality/value – Originality of this research is in finding out the influence of Social Needs towards Dependence on Smartphone and Purchase Intention